Assessment of Building Seismic Risk in the Environment of Ibn Khaldun University Bogor - Lutfi, Muhamad; Chayati, Nurul; Rulhendri, Rulhendri; Azhari, Denny (ASTONJADRO, 2022)
The city of Bogor has varied contours and high rainfall. Potential natural disasters that often occur include floods, landslides, collapsed buildings, fires, landslides, hurricanes, earthquakes, and landslides. The city of Bogor is included in the zone 4 earthquake. Buildings in the Ibn Khaldun University (UIKA) Bogor were erected vertically as an optimization of limited land. The study of the vulnerability of buildings to earthquakes is very important to ensure that building users are in a safe condition during the service life of buildings against earthquakes using the Rapid Visual Screening (RVS) Method and the Hazus Method. The RVS form is obtained from the design spectra and the response spectrum, namely the high seismicity level based on the building coordinates. Based on the results of the RVS, the value of the vulnerability of buildings in the UIKA Bogor environment is 0.086% with an average value of 3.156. Based on the inspection that has been carried out, the buildings are classified as C1 and S1 building types, vertical irregularities occur in 3 buildings, plan irregularities occur in 1 building out of a total of 9 buildings and the land is assumed to be medium soil (type D) because there is no soil investigation.